Solving the 31P1H NMR spectrum of (Me3Si)3P7 as B[AC]3 case. (3rd June 2017) - Matern, Eberhard; Engelhardt, Michael; Hägele, Gerhard
GRAPHICAL ABSTRACT: ABSTRACT: 31 P NMR chemical shifts and coupling constants of (Me3 Si)3 P7 in solution state reveal C3 symmetry which is consistent with a twisted molecular framework as found in solid state. The 31 P 1 H NMR spectrum was iterated as a B[AC]3 system by automated line shape analysis usingDAISY underTOPSPIN .